112 Rational design of chimeric antigen receptor T cells against glypican 3 decouples toxicity from therapeutic efficacy. (9th November 2020) - Giardino, Letizia; Gilbreth, Ryan; Chen, Cui; Sult, Erin; Monks, Noel; Tammali, Ravinder; Chesebrough, Jon; Schifferli, Kevin; Chu, Nina; Tong, Jessica; Clarke, Lori; Gesse, Christina; et al.
Abstract : Background: Chimeric antigen receptor (CAR)-T therapy has yielded impressive clinical results in hematological malignancies and it is a promising approach for solid tumor treatment. However, toxicity, including on-target off-tumor antigen binding, is a concern hampering its broader use. Methods: In selecting a lead CAR-T candidate against the oncofetal antigen glypican 3 (GPC3), we compared CAR bearing a low and high affinity single-chain variable fragment (scFv, ) binding to the same epitope and cross-reactive with murine GPC3. We characterized low and high affinity CAR-T cells immunophenotype and effector function in vitro, followed by in vivo efficacy and safety studies in hepatocellular carcinoma (HCC) xenograft models. Results: Compared to the high-affinity construct, the low-affinity CAR maintained cytotoxic function but did not show in vivo toxicity. High-affinity CAR-induced toxicity was caused by on-target off-tumor binding, based on the evidence that high-affinity but not low-affinity CAR, were toxic in non-tumor bearing mice and accumulated in organs with low expression of GPC3. To add another layer of safety, we developed a mean to target and eliminate CAR-T cells using anti-TNFα antibody therapy post-CAR-T infusion. This antibody functioned by eliminating early antigen-activated CAR-T cells, but not all CAR-T cells, allowing a margin where the toxic response could be effectively decoupled from anti-tumor efficacy. Conclusions: Selecting a domain with higher off-rate improved the quality of the CAR-T cells by maintaining cytotoxic function while reducing cytokine production and activation upon antigen engagement. By exploring additional traits of the CAR-T cells post-activation, we further identified a mechanism whereby we could use approved therapeutics and apply them as an exogenous kill switch that would eliminate early activated CAR-T following antigen engagement in vivo. By combining the reduced affinity CAR with this exogenous control mechanism, we provide evidence that we can modulate and control CAR-mediated toxicity. Ethics Approval: All animal experiments were conducted in a facility accredited by the Association for Assessment of Laboratory Animal Care (AALAC) under Institutional Animal Care and Use Committee (IACUC) guidelines and appropriate animal research approval.